The results of flow efficiency methodology in a labour-intensive, South African operation - Bodill, Chris (My University, 2016)
The research project aimed at determining employees’ experiences of the application of the flow efficiency methodology. The flow efficiency methodology was the selected management methodology from the broader scope of process-focused methodologies. The significance of the flow efficiency approach is that it’s an alternative approach to the traditional management approach of optimising resource efficiency, but rather focuses on improving the flow of the process in which the resources work. The research was conducted in the context of the labour-intensive, South African manufacturing sector using a case study approach. The purpose of the research was to understand front-line employees’ and supervisors’ perceptions during the application of the flow efficiency approach. The assessed perceptions came from four selected change factors that stemmed from the Lean change iceberg model commonly found in literature. The motivation for research was two-fold: (1) prior research of the flow efficiency methodology in the socio-technical environment focused on operational improvement impact, and not on the impact on people; and (2), most research of improvement approaches and methods in South Africa tended to focus on success factors and pre-requisite maturity levels of various methods. The chosen flow efficiency approach required no pre-requisite culture requirements. The researcher was of the view that gaining an insight (through a case study) into employees’ perceptions of change factors during a flow efficiency approach, could lead to benefits of development and empowerment of employees and management in the labour-intensive, manufacturing sector of South Africa. The case study selected was a flow efficiency-based, improvement initiative in a multinational dairy plant in South Africa. The researcher used an unstructured, group-administered questionnaire to assess operational and supervisory employees’ perceptions of the selected change factors after process changes were made in the process where they work. The four selected process-improvement change factors derived from the Lean change iceberg were: Leadership Behaviour; Social System Change; Effectiveness of Change; and Employee Involvement & Empowerment. Content validity was conducted with external and internal experts to refine the questions and sequence of the questionnaire. A trained research assistant facilitated the multiple questionnaire sessions. Thematic content analysis was used to categorise participant’s responses into themes and sub-themes for each question. The occurrence of themes and sub-themes per question was tallied up and discussed for operational and supervisory employees with respect to the research objectives. The research did not yield a broad-based view on the impact of the flow efficiency management approach on employees’ perceptions in the greater industry context. However, it did give an insight, through the case study, into some universally applicable perceptions of changes experienced by South African, front-line and supervisory employees when the flow efficiency management approach was used. Perceptions of: leadership commitment and coaching, improved teamwork, simplification of jobs, improved flow, and improvements in individual performance, and employee empowerment were prevalent perceptions felt by most employees at both levels.
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in fulfilment of the requirements for the degree of Masters in Science in Industrial Engineering. October 2016
Keywords: Lean manufacturing; Organizational effectiveness--Evaluation; Organizational effectiveness--South Africa; Labor productivity--South Africa; Industrial efficiency